Measurement and modelling of the transient thermal-mechanical strain field during GMA welding - Coules, Harry E.; Cozzolino, Luis D.; Colegrove, Paul A.; Wen, S. W. (Cranfield University, 2011)
The state of residual stress in welded joints is a well-studied topic, and many methodsof residual stress measurement are now available. However, far less is known aboutthe transient strains which occur during the welding process, even though these are thedirect cause of residual stresses. Efforts to model welding processes usually includetransient stresses and strains among their results, but in general these models can onlybe easily compared against experimentally measured residual stresses: there is a lackof published data covering strain in the transient regime.In this study, electrical resistance strain gauges were used to measure transient strainsduring welding, and comparison is made between these measurements and the resultsfrom a sequential thermo-mechanical finite element model of the process. Well-definedmechanical boundary conditions were used for the experiments to ease interpretationof the measured strain data, and to enable close approximation with the boundaryconditions of the computational model. The transient biaxial state of strain wasmeasured during Gas Metal Arc Welding (GMAW) of S355 steel samples in a bead-onplateconfiguration. Measured transient strains were found to be consistent betweensamples, and showed good agreement with the modelling results. It is hoped thatfuture study of welding transient strains will aid in the optimisation of in-processmethods to reduce residual stress, such as rolling and quench cooling.